Preparation method of single-component water-oil mixed type environment-friendly composite adhesive

By synergistic pretreatment of nanocellulose and montmorillonite and graphene quantum dot-chitosan composite modification materials, combined with gradient polymerization and ultrasonic composite processes, a single-component water-oil mixed environmentally friendly composite adhesive was prepared. This solved the problems of cumbersome operation and poor environmental performance of traditional adhesives, and achieved a high-strength, water-resistant, and high-production-efficiency adhesive, thus expanding its application scenarios.

CN120966400AInactive Publication Date: 2025-11-18德清县虎马中环佳科技股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511105399.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2025-11-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Most existing composite adhesives are two-component, which are cumbersome to operate and difficult to guarantee the accuracy of the ratio. Single-component water-oil mixed adhesives have problems such as poor environmental performance, complicated preparation steps, low reaction efficiency, insufficient product bonding strength, and poor water resistance.

Method used

By employing synergistic pretreatment of nanocellulose and montmorillonite, combined with graphene quantum dot-chitosan composite modified materials, a single-component water-oil mixed environmentally friendly composite adhesive was prepared through gradient polymerization, ultrasonic compounding, and low-temperature curing processes. This process achieves uniform dispersion of fillers, improves bonding strength and water resistance, and enhances the compatibility of the water and oil phases through ultrasonic treatment, thereby reducing the amount of emulsifier used and energy consumption.

Benefits of technology

It significantly improves the bonding strength and water resistance of adhesives, shortens production time, reduces energy consumption and emulsifier usage, improves production efficiency and product stability, meets application needs in different environments, and complies with environmental standards for green building and food packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120966400A_ABST
    Figure CN120966400A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a single-component water-oil mixed type environment-friendly composite adhesive. The preparation method comprises the following steps: S1, a synergistic pretreatment stage; s2, a gradient polymerization stage; s3, an ultrasonic compounding stage; and S4, a low-temperature curing stage. Through the synergistic effect of the nanocellulose and the montmorillonite, modification of the green coupling agent and the graphene quantum dot-chitosan composite modified material, the problem that a traditional filler is prone to agglomeration is solved, the filler is evenly dispersed in the adhesive, the mechanical property of the adhesive is greatly improved, the gradient polymerization process has the advantages that the temperature is accurately controlled, and the mechanical property of the adhesive is greatly improved. According to the present invention, the monomer conversion rate is increased to more than 98%, the molecular weight distribution of the product is uniform, the stability of the bonding strength is ensured, the bonding strength can achieve 4.2 MPa, the strength retention rate can still achieve 92% in the temperature cycle test of-20-60 DEG C, the application reliability in different environments is ensured, and the high requirements on the adhesive performance in the fields of building, packaging and the like are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mechanical technology, and in particular to a method for preparing a single-component water-oil mixed environmentally friendly composite adhesive. Background Technology

[0002] Currently, the composite adhesive market is dominated by oil-based acrylic and rubber-based composite adhesives, accounting for about 80% of the composite adhesive field. Oil-based composite adhesives have excellent initial tack, water resistance, flexibility, and fast evaporation to form a film.

[0003] Most composite adhesives currently on the market are two-component, requiring on-site mixing, which is cumbersome and makes it difficult to guarantee precise proportions. While single-component adhesives are convenient to use, traditional single-component water-oil mixed adhesives have the following problems: the preparation process requires large amounts of organic solvents or toxic emulsifiers, resulting in poor environmental performance; the preparation steps are complex, the reaction efficiency is low, and the product has insufficient bonding strength and poor water resistance. Therefore, this invention proposes a method for preparing a single-component water-oil mixed environmentally friendly composite adhesive. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing technologies by proposing a method for preparing a single-component water-oil mixed environmentally friendly composite adhesive.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] A method for preparing a single-component water-oil mixed environmentally friendly composite adhesive includes the following steps:

[0007] S1. Synergistic Pretreatment Stage: In the synergistic pretreatment stage, nanocellulose and montmorillonite are added to deionized water at a mass ratio of 1:0.5-2. After stirring and dispersing for 10-15 minutes, 3-5% of a green coupling agent (by mass of nanocellulose) and 2-4% of a graphene quantum dot-chitosan composite modifier (by mass of nanocellulose) are added. The mixture is then ultrasonically treated at 30-40℃ with a power of 250-350W for 20-30 minutes to obtain a synergistically modified filler dispersion.

[0008] S2, Gradient Polymerization Stage: Deionized water, acrylate monomers, and a composite initiator accounting for 2-3% of the total monomer mass are added to the reactor. The composite initiator is a mixture of ammonium persulfate and vitamin C at a mass ratio of 2:1. The reaction is first carried out at 50-55℃ for 1-1.5 hours, and then the temperature is raised to 65-70℃ for 2-2.5 hours. During the reaction, nitrogen gas is introduced to remove oxygen at a flow rate of 1.5-3 L / min for 8-15 minutes to form a basic emulsion. The acrylate monomers are a mixture of methyl methacrylate and butyl acrylate at a mass ratio of 2:1-4:1.

[0009] S3, Ultrasonic Composite Stage: The synergistic modified filler dispersion is slowly added to the base emulsion at a flow rate of 3-6 L / min. At the same time, the ultrasonic equipment is turned on and ultrasonic treatment is carried out at a power of 200-300W for 30-40 minutes. When the ultrasonic treatment is carried out for 5-15 minutes, a green emulsifier accounting for 1-2% of the total mass of the system is added. The green emulsifier is sucrose fatty acid ester to form a composite emulsion.

[0010] S4. Low-temperature curing stage: The composite emulsion is allowed to stand and cure at 30-35℃ for 4-5 hours. During the curing process, at least one parameter of the emulsion viscosity, pH value or particle size is tested every 1-2 hours. Then, it is filtered with an 80-120 mesh filter and metered and packaged to obtain a single-component water-oil mixed environmentally friendly composite adhesive.

[0011] Preferably, the preparation steps of the graphene quantum dot-chitosan composite modified material are as follows:

[0012] Step 1: Add 0.5g of graphene quantum dots to 50mL of deionized water and ultrasonically disperse at 300W for 30 minutes to obtain a graphene quantum dot dispersion.

[0013] Step 2: Add 2g of chitosan to 100mL of 1% acetic acid solution and stir at 60℃ until completely dissolved to obtain a chitosan solution;

[0014] Step 3: Slowly add the graphene quantum dot dispersion obtained in Step 1 to the chitosan solution obtained in Step 2 at a rate of 1-2 drops / second. Stir the mixture at 400-500 r / min for 2 hours at 50℃. Then, perform vacuum freeze-drying under the following conditions: -50℃, vacuum degree 10 Pa, and drying time 24 hours. After drying, grind the mixture into powder with a particle size of 50-100 μm to obtain the graphene quantum dot-chitosan composite modified material.

[0015] Preferably, in the synergistic pretreatment stage, the mass ratio of nanocellulose to montmorillonite is 1:0.8, and the ultrasonic treatment power is 250W; in the gradient polymerization stage, the acrylate monomers are methyl methacrylate and butyl acrylate mixed at a mass ratio of 2:1, the nitrogen flow rate in the reactor is 1.8L / min, and the oxygen removal time is 10 minutes.

[0016] Preferably, in the synergistic pretreatment stage, the amount of green coupling agent added accounts for 3.5% of the mass of nanocellulose, and the stirring and dispersion speed is 800 r / min; in the ultrasonic compounding stage, the injection flow rate of the synergistic modified filler dispersion is 3.5 L / min, and the green emulsifier is added after 8 minutes of ultrasonic treatment.

[0017] Preferably, in the synergistic pretreatment stage, the amount of graphene quantum dot-chitosan composite modified material added accounts for 3% of the mass of nanocellulose; in step one of the preparation of the graphene quantum dot-chitosan composite modified material, the vacuum freeze-drying conditions are -50℃, vacuum degree 10Pa, and drying time 24 hours.

[0018] Preferably, in the gradient polymerization stage, the acrylate monomers are methyl methacrylate and butyl acrylate mixed at a mass ratio of 4:1, and the reaction time at 50-55°C is 1.2 hours; in the low-temperature curing stage, the curing temperature is 33°C, and the pH value of the emulsion is detected every 1 hour, and the pH value is controlled between 7.2 and 7.5.

[0019] Preferably, in the gradient polymerization stage, the amount of composite initiator added accounts for 2.5% of the total monomer mass, and the monomer conversion rate is detected in real time by gas chromatography. The reaction is stopped when the conversion rate is ≥98%. In the synergistic pretreatment stage, the ultrasonic treatment temperature is 35°C and the treatment time is 25 minutes.

[0020] Preferably, in the ultrasonic composite stage, the injection flow rate of the synergistic modified filler dispersion is 4 L / min, and the ultrasonic treatment power is 250 W; in the gradient polymerization stage, the reaction time after heating to 65-70℃ is 2 hours, and the stirring speed of the reactor is 450 r / min.

[0021] Preferably, in the ultrasonic compounding stage, a green emulsifier is added 10 minutes after ultrasonic treatment, and the amount of green emulsifier added accounts for 1.5% of the total mass of the system; in the low-temperature maturation stage, the compound emulsion is allowed to stand for maturation for 4.2 hours and is filtered through a 90-mesh filter.

[0022] Preferably, in the low-temperature curing stage, the curing temperature is 32°C, the curing time is 4.5 hours, and the viscosity of the emulsion is detected every 1.5 hours, with the viscosity controlled between 5500-5800 mPa·s; in the synergistic pretreatment stage, the amount of deionized water added is 40 times the total mass of nanocellulose and montmorillonite.

[0023] The present invention has the following beneficial effects:

[0024] 1. By leveraging the synergistic effect of nanocellulose and montmorillonite, along with modification using green coupling agents and graphene quantum dots-chitosan composite materials, the problem of easy agglomeration of traditional fillers is solved, enabling uniform dispersion of fillers in adhesives and significantly improving the mechanical properties of the adhesives. The gradient polymerization process, through precise temperature control, increases the monomer conversion rate to over 98%, resulting in a more uniform molecular weight distribution and ensuring the stability of the bonding strength. The bonding strength reaches 4.2 MPa, a 50% improvement compared to ordinary methods. Furthermore, in temperature cycling tests from -20℃ to 60℃, the strength retention rate still reaches 92%, ensuring reliability in applications under different environments and meeting the high performance requirements of adhesives in various fields such as construction and packaging.

[0025] 2. The ultrasonic compounding stage integrates filler dispersion and emulsion compounding into one step. Utilizing the cavitation effect of ultrasound, it enhances the compatibility of the water-oil phase, reducing not only the cumbersome steps in traditional processes but also shortening production time. Simultaneously, this stage reduces emulsifier usage by over 30%, mitigating product stability issues caused by excessive emulsifier. The low-temperature curing stage uses a temperature of 30-35℃, compared to the traditional 50-60℃ curing temperature, reducing energy consumption by 40% and extending product shelf life to over 6 months. Through these optimized production processes, curing time is shortened to 14.4 hours, the cycle time of automated production line equipment is increased to 20 seconds per piece, and daily production capacity is increased by 50% compared to ordinary methods, significantly improving production efficiency and product stability.

[0026] 3. The graphene quantum dot-chitosan composite modified material is prepared from graphene quantum dots and natural high-molecular-weight chitosan. It exhibits excellent biocompatibility, with a biodegradability rate exceeding 85% within 3 months, avoiding the toxic residues of traditional chemical modifiers. The polar groups in its molecular structure can synergistically interact with green coupling agents and emulsifiers without affecting the system's environmental performance, maintaining the VOC content of the adhesive at a low level of 35-50 g / L. Graphene quantum dots possess extremely high surface energy and excellent dispersibility. The amino and hydroxyl groups on the chitosan molecular chain can bind with the functional groups on the surface of nanocellulose and montmorillonite through hydrogen bonds, forming a three-dimensional network structure that effectively prevents filler particle agglomeration. Experimental data shows that after adding this composite modified material, the particle size distribution uniformity of the synergistically modified filler dispersion is improved by 40%, and the sedimentation rate drops from 15% to below 5% after 72 hours of standing, solving the problem of poor stability in traditional filler dispersion systems. Attached Figure Description

[0027] Figure 1 This is a flowchart illustrating a method for preparing a single-component water-oil mixed environmentally friendly composite adhesive proposed in this invention.

[0028] Figure 2 The image shows the infrared signature of chitosan in the nanocellulose and graphene quantum dot-chitosan composite modified material of this invention.

[0029] Figure 3 This is a spectral mapping sequence of the alkyl structure in the acrylate monomer of the present invention;

[0030] Figure 4 This is a spectral color surface diagram of the alkyl structure in the acrylate monomer of this invention; Detailed Implementation

[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0032] Example 1: High Bonding Strength Type (Suitable for Bonding Building Panels)

[0033] Preparation steps:

[0034] S1. Synergistic pretreatment: Weigh 10 kg of nanocellulose and 15 kg of montmorillonite and add them to 500 L of deionized water. After stirring and dispersing at 850 r / min for 12 minutes, add 0.4 kg of γ-aminopropyltriethoxysilane modified product and 0.3 kg of graphene quantum dot-chitosan composite modified material. Sonicate at 35℃ with 300 W power for 25 minutes to obtain synergistic modified filler dispersion.

[0035] S2. Gradient Polymerization: Add 300L deionized water, 90kg methyl methacrylate, and 30kg butyl acrylate to a 1000L reactor and stir (500r / min) until homogeneous. Add 2.4kg of composite initiator (1.6kg ammonium persulfate and 0.8kg vitamin C), close the reactor, and purge with nitrogen at a flow rate of 2L / min for 10 minutes. First, heat the reactor to 52℃ and maintain the temperature for 1.2 hours; then heat to 68℃ and continue the reaction for 2.3 hours. During this period, sample and test the monomer conversion rate every 30 minutes (by gas chromatography). Stop the reaction when the conversion rate is ≥98% to obtain the base emulsion.

[0036] S3. Ultrasonic compounding: The synergistically modified filler dispersion is slowly injected into the base emulsion using a metering pump at a flow rate of 5 L / min. Simultaneously, the ultrasonic device is turned on at a power of 250 W, and ultrasonic treatment is performed for 35 minutes. After 10 minutes of ultrasonic treatment, 3.6 kg of sucrose fatty acid ester is added, and stirring is continued (600 r / min) until the ultrasonic treatment ends, forming a composite emulsion.

[0037] S4. Low-temperature curing: Transfer the composite emulsion to a curing tank and allow it to stand at 32°C for 4.5 hours. During this period, the emulsion viscosity is measured every hour using a rotational viscometer (NDJ-1 type). After curing, filter the emulsion through a 100-mesh filter to remove impurities. Finally, use an automatic filling machine to weigh and package the emulsion (20kg per barrel) to obtain the finished product.

[0038] In this embodiment, the graphene quantum dot-chitosan composite modified material forms a stronger hydrogen bond network with nanocellulose and montmorillonite, increasing the bonding strength from 4.2 MPa to 4.8 MPa and the impact strength by 20%. In vibration tests of building panels, no fatigue damage was observed at the bonding interface, representing an improvement of over 30% compared to traditional building adhesives. In bonding tests on building panels such as gypsum board and MDF, after 72 hours of constant temperature and humidity, no cracking or peeling occurred at the bonding interface, meeting the stringent structural stability requirements of high-rise buildings.

[0039] Furthermore, the single-component form eliminates the need for on-site mixing, improving construction efficiency by 40%. The adhesive achieves an initial tack of 0.8 MPa, enabling preliminary fixation of boards within 30 minutes of application, reducing the need for auxiliary support procedures during construction. After 100 cycles of temperature cycling from -20℃ to 60℃, the bond strength retention rate reaches 92%, solving the problem of traditional adhesives becoming brittle and detaching under extreme temperatures. The VOC content is as low as 45 g / L, far below the national standard of 100 g / L, and there is no irritating odor during construction, meeting the requirements for green building material certification.

[0040] Example 2: High water resistance type (suitable for packaging in humid environments)

[0041] Preparation steps:

[0042] S1. Synergistic pretreatment: Weigh 8 kg of nanocellulose and 6.4 kg of montmorillonite and add them to 400 L of deionized water. After stirring and dispersing at 750 r / min for 10 minutes, add 0.28 kg of γ-aminopropyltriethoxysilane modified product and 0.24 kg of graphene quantum dot-chitosan composite modified material. Sonicate at 38 °C with 250 W power for 22 minutes to obtain synergistic modified filler dispersion.

[0043] S2. Gradient polymerization: Add 250L of deionized water, 60kg of methyl methacrylate, and 30kg of butyl acrylate to an 800L reactor and mix by stirring (450 rpm). Add 1.8kg of composite initiator (1.2kg of ammonium persulfate and 0.6kg of vitamin C), purge with nitrogen at a flow rate of 1.5L / min for 8 minutes. React at 50℃ for 1 hour, then increase the temperature to 65℃ and react for 2 hours. Stop the reaction when the monomer conversion rate is ≥97% to obtain the basic emulsion.

[0044] S3. Ultrasonic compounding: Inject the synergistically modified filler dispersion into the base emulsion at a flow rate of 4 L / min, and treat with a 200W ultrasonic device for 30 minutes. After 5 minutes of ultrasonication, add 1.8 kg of sucrose fatty acid ester, and keep stirring (550 r / min) to form a composite emulsion;

[0045] S4. Low-temperature curing: Place the composite emulsion in a curing tank at 30℃ and let it stand for 5 hours. Check the pH value every 2 hours and control it between 7 and 8. After curing, filter through an 80-mesh filter and package (10kg per barrel).

[0046] In this embodiment, the composite modified material enhances the hydrophobic barrier at the water-oil interface, increasing the strength retention rate from 95% to 97% after 72 hours of immersion in water. After 30 days of storage in a constant humidity (90% RH) environment at 40°C, the emulsion separation rate is <1%, a 60% reduction compared to when no material was added. In food refrigerated packaging, such as vacuum packaging of meat, after repeated freeze-thaw cycles (-18°C freezing / 25°C thawing) 20 times, the packaging sealing performance showed no degradation, effectively preventing food spoilage caused by moisture penetration.

[0047] Furthermore, the compatibility between the water and oil phases is improved, and the emulsion shows no stratification after standing for 30 days. Its storage stability is superior to traditional products, which are prone to stratification within 15 days. It uses food-grade emulsifier sucrose fatty acid ester, and the content of heavy metals such as lead and cadmium is less than 0.01 mg / kg, which meets the GB4806.10-2016 standard for food contact adhesives. Although the cost is slightly higher than that of ordinary packaging adhesives by 5%, it reduces the packaging breakage rate from the traditional 8% to below 2%, resulting in a 12% reduction in overall usage cost.

[0048] Example 3: Rapid Curing Type (Suitable for Automated Production Lines)

[0049] Preparation steps:

[0050] S1. Synergistic pretreatment: Weigh 12kg of nanocellulose and 24kg of montmorillonite and add them to 600L of deionized water. After stirring and dispersing at 900r / min for 15 minutes, add 0.6kg of γ-aminopropyltriethoxysilane modified product and 0.48kg of graphene quantum dot-chitosan composite modified material. Sonicate at 40℃ with 350W power for 30 minutes to obtain synergistic modified filler dispersion.

[0051] S2. Gradient polymerization: Add 400L deionized water, 120kg methyl methacrylate, and 40kg butyl acrylate to a 1500L reactor and mix by stirring (600r / min). Add 4.8kg composite initiator, 3.2kg ammonium persulfate, and 1.6kg vitamin C. Purge with nitrogen at a flow rate of 3L / min for 15 minutes. React at 55℃ for 1.5 hours, then raise the temperature to 70℃ and react for another 2.5 hours, ensuring a monomer conversion rate ≥98.5%, to obtain the basic emulsion.

[0052] S3, Ultrasonic Composite: Inject the synergistically modified filler dispersion into the base emulsion at a flow rate of 6 L / min, and treat with a 300W ultrasonic device for 40 minutes. After 15 minutes of ultrasonication, add 6 kg of sucrose fatty acid ester and stir (700 r / min) until the ultrasonication ends to form a composite emulsion;

[0053] S4. Low-temperature curing: The composite emulsion is left to stand in a curing tank at 35℃ for 4 hours. During this period, the particle size of the emulsion is measured using a laser particle size analyzer, requiring a D50 between 100-200nm. After curing, it is filtered through a 120-mesh filter and then packaged (25kg per drum).

[0054] In this embodiment, the catalytic activity of the composite modified material accelerates the curing reaction rate, shortening the curing time from 14.4 hours to 13 hours, and increasing the crosslinking density of the cured adhesive layer by 15%. In continuous operation tests on the automated production line, the equipment downtime cleaning cycle is extended to 72 hours (from 60 hours). In the automated board bonding production line, the equipment cycle time can be increased from 30 seconds / piece to 20 seconds / piece, increasing the daily production capacity by more than 5,000 pieces. Due to the shortened curing cycle, the energy consumption of the drying process is reduced by 35%.

[0055] Furthermore, in automated production lines, the curing rate deviation of the adhesive is controlled within ±5%, which is much lower than ±15% of traditional products. This reduces the defect rate caused by uneven curing from 3% to 0.5%. The adhesive viscosity is stable at 5000-6000 mPa·s at 25℃, making it compatible with existing automated equipment such as spraying and roller coating, without the need for additional production line modifications.

[0056] Example 4: Low VOC Economy (Suitable for Food Packaging)

[0057] Preparation steps:

[0058] S1. Synergistic pretreatment: Weigh 5 kg of nanocellulose and 2.5 kg of montmorillonite and add them to 200 L of deionized water. Stir and disperse at 700 r / min for 10 minutes. Then add 0.15 kg of γ-aminopropyltriethoxysilane modified product and 0.1 kg of graphene quantum dot-chitosan composite modified material. Ultrasonically treat at 30 °C with 220 W power for 20 minutes to obtain synergistic modified filler dispersion.

[0059] S2. Gradient polymerization: Add 150L of deionized water, 45kg of methyl methacrylate, and 15kg of butyl acrylate to a 500L reactor and mix by stirring (480 rpm). Add 1.2kg of composite initiator, 0.8kg of ammonium persulfate, and 0.4kg of vitamin C. Purge with nitrogen gas at a flow rate of 1.8L / min for 12 minutes. After reacting at 50℃ for 1 hour, raise the temperature to 65℃ and react for 2 hours. Stop the reaction when the monomer conversion rate is greater than or equal to 97% to obtain the basic emulsion.

[0060] S3. Ultrasonic compounding: Inject the synergistically modified filler dispersion into the base emulsion at a flow rate of 3 L / min, and treat with a 200W ultrasonic device for 30 minutes. After 8 minutes of ultrasonication, add 1.5 kg of sucrose fatty acid ester and stir (580 r / min) until the ultrasonication ends to form a composite emulsion;

[0061] S4. Low-temperature curing: The compound emulsion is left to stand in a curing tank at 30℃ for 4 hours. After curing, the VOC content is tested using gas chromatography-mass spectrometry to ensure it is ≤35g / L. After filtration through a 100-mesh filter, it is aseptically filled and packaged (15kg per drum).

[0062] In this embodiment, the composite modified material replaces part of the nanofiller, reducing the raw material cost by 3% while maintaining the VOC content at 35g / L. The light transmittance of the adhesive layer is increased to 92% (from 88%), making it more suitable for transparent food packaging. After 6 months of storage, the emulsion viscosity fluctuation is ≤5% (from 8%). Migration tests show that the migration of harmful substances such as formaldehyde and benzene compounds is less than 0.01mg / kg, which meets the FDA food contact material standards.

[0063] Furthermore, the raw material cost is reduced by 10%, mainly due to the optimized use of nanofillers (reduced by 30%), lower process energy consumption (energy saving of 40% during the low-temperature curing stage), and the adhesive forming a transparent film after curing, which does not affect the appearance of the food packaging. In oil resistance tests, it showed no swelling or discoloration within 30 days of contact with vegetable oil, making it suitable for packaging oily foods such as fried foods and sauces. Under light-protected storage conditions at 25℃, the shelf life reaches more than 6 months, extending the lifespan of traditional food packaging adhesives by 50% compared to 3-4 months, reducing waste caused by product expiration.

[0064] Table 1: Comparison of Environmental Performance Data between Various Embodiments and Conventional Methods

[0065]

[0066]

[0067] Table 2: Comparison of Mechanical and Weather Resistance Data of Each Embodiment and the Ordinary Method

[0068]

[0069] Table 3: Comparison of Production and Storage Performance Data between Each Embodiment and the Conventional Method

[0070]

[0071] Table 4: Comparison of cost-related data between various embodiments and the conventional method

[0072]

[0073]

[0074] Based on the above embodiments and tables, it can be seen that the VOC content of the conventional preparation method reaches 100g / L, far exceeding the environmental protection standard. During production and use, it releases a large amount of harmful gases, adversely affecting the health of operators and the surrounding environment. In contrast, the VOC content of the four specific embodiments of this invention is as low as 35g / L (Embodiment 4) and as high as 50g / L (Embodiment 3), both significantly lower than that of the conventional method. Based on an annual production of 1000 tons of adhesive, the conventional method emits approximately 100 tons of VOCs annually, while Embodiment 4 emits only 35 tons, reducing harmful gas emissions by 65 tons. Furthermore, the green coupling agent and emulsifier used are biodegradable, achieving a degradation rate of over 90% within three months in the natural environment. This avoids the pollution of soil and water sources caused by traditional chemical additives, contributing to the transformation of the adhesive industry towards environmental protection and sustainability.

[0075] Furthermore, regarding bonding strength, conventional methods only achieve 2.8 MPa, which is insufficient to meet the high-strength bonding requirements of high-rise building panels. Implementation Method 1, through optimized raw material ratios and processes, increases the bonding strength to 4.2 MPa, a 50% improvement over conventional methods. In practical applications, it can withstand a static load of 500 kg per square meter, successfully solving the problem of loosening and detachment of large building panels after installation. In terms of water resistance, conventional methods retain only 75% of their strength after 72 hours of immersion in water, and are prone to bonding failure in humid environments. Implementation Method 2 achieves 95% of this indicator. In food refrigerated packaging scenarios, after 30 consecutive days of low-temperature and high-humidity environment testing, the packaging seal integrity rate reached 100%, a 30% improvement over conventional methods. This effectively prevents food spoilage due to packaging damage and significantly broadens the application range of adhesives in humid and high-humidity environments.

[0076] Furthermore, the conventional method has a curing time of 24 hours, and the automated production line equipment has a cycle time of 30 seconds per piece, resulting in low production efficiency and difficulty in meeting the needs of large-scale industrial production. Implementation method three shortens the curing time to 14.4 hours and increases the equipment cycle time to 20 seconds per piece. Based on 24-hour production, the conventional method has a daily capacity of approximately 2880 pieces, while implementation method three can reach 4320 pieces, increasing daily capacity by 50%. This translates to an additional approximately 520,000 pieces per year, significantly improving the company's order response speed. In terms of cost, implementation method four reduces raw material costs by 10%, saves 82,000 yuan in electricity costs annually, and reduces overall operating costs by 9%. Taking a company with annual sales of 10 million yuan as an example, implementing implementation method four can increase profits by approximately 900,000 yuan annually. Based on the 9% reduction in overall costs, this significantly enhances the product's price competitiveness in the market and helps the company expand its market share.

[0077] In addition, from an environmental perspective, all four embodiments have achieved a breakthrough reduction in VOC content, with emissions of 35-50 g / L, a 50%-65% reduction compared to the 100 g / L of ordinary methods. Combined with biodegradable green additives, the degradation rate is over 90% in 3 months. A full life-cycle environmental protection system has been built from the source of production to the end of use, which can reduce the emissions of harmful gases by tens of tons per year, providing a replicable solution for the green transformation of the adhesive industry.

[0078] Furthermore, at the core performance level, each embodiment achieves precise breakthroughs for different scenario requirements: the high-bonding-strength type (Example 1) increases the strength to 4.2MPa, solving the high-strength bonding problem in the construction field; the high-water-resistance type (Example 2) achieves a 95% immersion strength retention rate, overcoming the pain point of packaging seal failure in humid environments; the fast-curing type (Example 3) has a curing cycle of 14.4 hours and a production cycle of 20 seconds per piece, meeting the high-efficiency requirements of automated production lines; and the low-VOC economic type (Example 4) balances cost while ensuring environmental friendliness. This "performance customization" characteristic expands the product's application scenarios from traditional fields to high-end scenarios such as high-rise buildings, food refrigeration, and automated manufacturing, increasing the application boundaries by more than 60%.

[0079] Furthermore, through process innovations such as gradient polymerization and ultrasonic compounding, the production efficiency of the four embodiments is increased by 30%-50% compared to ordinary methods, with a maximum daily capacity increase of 50%. Energy-saving processes such as low-temperature curing save 75,000-82,000 yuan in annual electricity costs. Combined with a 10% reduction in raw material costs (Example 4) and a reduction in packaging breakage rate to 2%, the overall cost of use decreases by 8%-12%. Taking a company with annual sales of 10 million yuan as an example, using the method of this invention can generate an additional profit of 700,000-900,000 yuan. At the same time, with a storage period of 6 months, which is 50% longer than that of ordinary methods, inventory losses are significantly reduced.

[0080] According to the instruction manual Figure 2-3 It can be determined that 3300-3400cm -1 The strong, broad peak originates from the -OH group in nanocellulose, 1720-1730 cm⁻¹ -1 The strong peak corresponds to the ester group (C=O) of acrylate monomers, 1160-1180 cm⁻¹ -1 The peak represents the ether bond of the green coupling agent, while the newly added weak peak at 1550-1600 cm⁻¹ represents the hydrogen bonding peak between amino and hydroxyl groups in the graphene quantum dot-chitosan composite modified material. The synergistic appearance of these peaks indicates that nanocellulose, the coupling agent, and the composite modified material form a stable multi-component network structure.

[0081] Additionally, through the instruction manual Figure 2 and instruction manual attached Figure 4 It is understood that 950-1100cm -1 The Si-OC peak originates from the green coupling agent, 780-800 cm⁻¹ -1 The peak is Si-O-Si of montmorillonite, 1580 cm⁻¹ -1 The nearby peaks are characteristic amino peaks of chitosan in the graphene quantum dot-chitosan composite modified material. The enhanced synergistic effect of silicon-oxygen bonds and amino groups reflects the good combination of inorganic and organic phases in the water-resistant modification, while the 1630 cm⁻¹ peak... -1 The extremely weak C=C peak indicates a high monomer conversion rate (2950-2850 cm⁻¹). -1 The alkyl peaks are strong and sharp, and the graphene quantum dot-chitosan composite modified material has a peak length of 1380 cm⁻¹. -1 The clear methyl bending vibration peak indicates that the organic segments in the material are arranged in a regular manner, which is beneficial to the structural stability after rapid curing.

[0082] Also, 3350cm -1 The low intensity of the -OH peak corresponds to a small amount of nanocellulose used; the long-chain alkyl peak at 720 cm⁻¹ originates from a green emulsifier; and the 1080 cm⁻¹ peak of the graphene quantum dot-chitosan composite modified material... -1 The superposition of ether bond peaks and ester group peaks indicates that the material composition is simple and has good compatibility, which meets the characteristics of low VOC formulation.

[0083] In summary, the aforementioned specific implementation methods, through innovative preparation processes and raw material selection, demonstrate advantages far exceeding those of traditional methods in multiple aspects. Their VOC content is significantly reduced to only 35-50 g / L, and they utilize biodegradable green additives, constructing a comprehensive environmental protection system throughout the entire lifecycle. Targeted breakthroughs have been achieved in core performance aspects, including high bonding strength, high water resistance, and rapid curing, expanding application scenarios. Production efficiency is increased by 30%-50%, and overall operating costs are reduced by 8%-12%, combining environmental, performance, and economic advantages.

[0084] It has achieved multiple goals, including "environmental compliance, performance upgrades, efficiency improvements, and cost optimization." It not only brings significant economic benefits to enterprises but also drives the adhesive industry towards a low-carbon, high-efficiency, and high-value-added transformation. Its technological advancement and market promotion value are significant, providing a high-quality solution for industry development.

[0085] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a single-component water-oil mixed environmentally friendly composite adhesive, characterized in that, Includes the following steps: S1. Synergistic pretreatment stage: Add nanocellulose and montmorillonite to deionized water at a mass ratio of 1:0.5-2, stir and disperse for 10-15 minutes, then add 3-5% of green coupling agent (by mass of nanocellulose) and 2-4% of graphene quantum dot-chitosan composite modifier (by mass of nanocellulose), and ultrasonically treat at 30-40℃ with a power of 250-350W for 20-30 minutes to obtain a synergistically modified filler dispersion. S2, Gradient Polymerization Stage: Deionized water, acrylate monomers, and a composite initiator accounting for 2-3% of the total monomer mass are added to the reactor. The composite initiator is a mixture of ammonium persulfate and vitamin C at a mass ratio of 2:

1. The reaction is first carried out at 50-55℃ for 1-1.5 hours, and then the temperature is raised to 65-70℃ for 2-2.5 hours. During the reaction, nitrogen gas is introduced to remove oxygen at a flow rate of 1.5-3 L / min for 8-15 minutes to form a basic emulsion. The acrylate monomers are a mixture of methyl methacrylate and butyl acrylate at a mass ratio of 2:1-4:

1. S3, Ultrasonic Composite Stage: The synergistic modified filler dispersion is slowly added to the base emulsion at a flow rate of 3-6 L / min. At the same time, the ultrasonic equipment is turned on and ultrasonic treatment is carried out at a power of 200-300W for 30-40 minutes. When the ultrasonic treatment is carried out for 5-15 minutes, a green emulsifier accounting for 1-2% of the total mass of the system is added. The green emulsifier is sucrose fatty acid ester to form a composite emulsion. S4. Low-temperature curing stage: The composite emulsion is allowed to stand and cure at 30-35℃ for 4-5 hours. During the curing process, at least one parameter of the emulsion viscosity, pH value or particle size is tested every 1-2 hours. Then, it is filtered with an 80-120 mesh filter and metered and packaged to obtain a single-component water-oil mixed environmentally friendly composite adhesive.

2. The preparation method of a single-component water-oil mixed environmentally friendly composite adhesive according to claim 1, characterized in that, The preparation steps of the graphene quantum dot-chitosan composite modified material are as follows: Step 1: Add 0.5g of graphene quantum dots to 50mL of deionized water and ultrasonically disperse at 300W for 30 minutes to obtain a graphene quantum dot dispersion. Step 2: Add 2g of chitosan to 100mL of 1% acetic acid solution and stir at 60℃ until completely dissolved to obtain a chitosan solution; Step 3: Slowly add the graphene quantum dot dispersion obtained in Step 1 to the chitosan solution obtained in Step 2 at a rate of 1-2 drops / second. Stir the mixture at 400-500 r / min for 2 hours at 50℃. Then, perform vacuum freeze-drying under the following conditions: -50℃, vacuum degree 10 Pa, and drying time 24 hours. After drying, grind the mixture into powder with a particle size of 50-100 μm to obtain the graphene quantum dot-chitosan composite modified material.

3. The preparation method of a single-component water-oil mixed environmentally friendly composite adhesive according to claim 1, characterized in that, In the synergistic pretreatment stage, the mass ratio of nanocellulose to montmorillonite is 1:0.8, and the ultrasonic treatment power is 250W; in the gradient polymerization stage, the acrylate monomers are methyl methacrylate and butyl acrylate mixed at a mass ratio of 2:1, the nitrogen flow rate in the reactor is 1.8L / min, and the oxygen removal time is 10 minutes.

4. The preparation method of a single-component water-oil mixed environmentally friendly composite adhesive according to claim 1, characterized in that, In the synergistic pretreatment stage, the amount of green coupling agent added accounts for 3.5% of the mass of nanocellulose, and the stirring and dispersion speed is 800 r / min; in the ultrasonic compounding stage, the injection flow rate of the synergistic modified filler dispersion is 3.5 L / min, and the green emulsifier is added after 8 minutes of ultrasonic treatment.

5. The preparation method of a single-component water-oil mixed environmentally friendly composite adhesive according to claim 2, characterized in that, In the synergistic pretreatment stage, the amount of graphene quantum dot-chitosan composite modified material added accounts for 3% of the mass of nanocellulose; in step one of the preparation of the graphene quantum dot-chitosan composite modified material, the vacuum freeze-drying conditions are -50℃, vacuum degree 10Pa, and drying time 24 hours.

6. The preparation method of a single-component water-oil mixed environmentally friendly composite adhesive according to claim 1, characterized in that, In the gradient polymerization stage, the acrylate monomers are methyl methacrylate and butyl acrylate mixed at a mass ratio of 4:1, and the reaction time at 50-55℃ is 1.2 hours. In the low-temperature curing stage, the curing temperature is 33℃, and the pH value of the emulsion is detected every 1 hour, and the pH value is controlled between 7.2 and 7.

5.

7. The preparation method of a single-component water-oil mixed environmentally friendly composite adhesive according to claim 1, characterized in that, In the gradient polymerization stage, the amount of composite initiator added accounts for 2.5% of the total monomer mass. The monomer conversion rate is detected in real time by gas chromatography, and the reaction is stopped when the conversion rate is ≥98%. In the synergistic pretreatment stage, the ultrasonic treatment temperature is 35℃ and the treatment time is 25 minutes.

8. The preparation method of a single-component water-oil mixed environmentally friendly composite adhesive according to claim 1, characterized in that, In the ultrasonic composite stage, the injection flow rate of the synergistic modified filler dispersion is 4 L / min, and the ultrasonic treatment power is 250 W; in the gradient polymerization stage, the reaction time after heating to 65-70℃ is 2 hours, and the stirring speed of the reactor is 450 r / min.

9. The preparation method of a single-component water-oil mixed environmentally friendly composite adhesive according to claim 1, characterized in that, In the ultrasonic compounding stage, a green emulsifier is added 10 minutes after ultrasonic treatment, and the amount of green emulsifier added accounts for 1.5% of the total mass of the system; in the low-temperature maturation stage, the compound emulsion is allowed to stand for maturation for 4.2 hours and is filtered through a 90-mesh filter.

10. The method for preparing a single-component water-oil mixed environmentally friendly composite adhesive according to claim 1, characterized in that, In the low-temperature curing stage, the curing temperature is 32℃ and the curing time is 4.5 hours. The viscosity of the emulsion is measured every 1.5 hours and the viscosity is controlled between 5500-5800 mPa·s. In the synergistic pretreatment stage, the amount of deionized water added is 40 times the total mass of nanocellulose and montmorillonite.